Pengaruh Ekstrak Metanol, Fraksi N-Heksana, dan Fraksi Metanol Biji Pepaya (Carica papaya L.) terhadap Kadar Testosteron dan Bobot Organ Reproduksi Tikus Jantan (Effect of Methanolic Extract, N-Hexanic Fraction, and Methanolic Fraction of Papaya Seed (Ca - Dwi Puspita Sari; Siti Muslichah; Wiratmo Wiratmo (Pustaka Kesehatan, 2014)
Papaya seeds (Carica papaya L.) was known have antifertility activity. Testosterone hormone and reproduction organs weight are influence antifertility activity. This study was conducted to compare the effect of the methanolic extract, fraction of n-hexane, and fraction of methanol papaya seeds ( dose 100 mg/kg BW ) with testosterone level and reproduction organs weight parameters of male rats. Measurement of testosterone level by ELISA method. The observation found that the three treatment didn’t decrease reproduction organs weight but decrease testosterone level compared to negative control group. Among the three treatments, metyhanolic extract and methanolic fraction decreased testosterone level. Extract and fraction of methanol alleged alkaloid content of which is known to inhibit development and count of spermatogenic cell.   Keywords: papaya seeds, testosterone, alkaloid, organ